Competition and control at work - rural miners and the labor process - Curtin, Chris; Shields, Dan (Economic & Social Studies, 1988)
For most of its short working life, the raining development at Tynagh, Co. Galway was characterised by `good? industrial relations. In explaining this phenomenon the authors of this paper suggest that while the structure of the labour process at the mine was such as to undermine worker solidarity, management control of the former was far from absolute and uncontested. It is further argued that worker-management relations were strongly influenced by factors external to the labour process. These included differences in the workers' class and spatial backgrounds, ambivalent attitudes to trade unions and the latters' inexperience with mining, the locality's dependence on the mine for employment and the alliance of the local elite and mine management.
Keywords: Industrial relations - Tynagh mines, Co. Galway; Management - Tynagh mines, Co. Galway